Teacher's Strategy in Dealing With Students' Misbehavior in SMPN 1 Lasalepa Subdistrict of Muna Regency - Rahmawati, Yuli; Sale, Firdaus; Suhartini, Lelly (Journal of Teaching English, 2019)
This study aimed at knowing the types of students’ misbehavior mostly happened in the learning process and strategy that teacher used in dealing with the students’ misbehavior at the first and second grade in SMPN 1 Lasalepa. The researcher employed descriptive as the design of the study where observation was used to collect the data. The results of the study showed that the misbehavior of students mostly happened in the class were: talking during the class, lack of concentration, joking, laziness, daydreaming, disobedience and running about the class. Then, teachers’ strategies used in dealing with the students’ misbehavior were: asking the students calmly but strictly to stop the students’ behavior problems, ignoring the students’ misbehavior and not paying attention to it, walking toward the student and getting physically close to them, and giving students questions in the classroom. As the result, it is necessary to be known due to problems always come in the class and teachers need to know the kinds of the problem and need to prepare the appropriate strategies to handle the problems properly in order to not disturb the learning process.